Victimology’s debt to Nils Christie: The outlasting legacy of a free thinker - Fattah Ezzat A. (Temida, 2016)
The tragic accidental death of Nils Christie was a huge loss to the scholarly worlds of criminology and victimology. An old dear friend and highly esteemed colleague, Christie has been hailed as one of the most innovative criminological thinkers of the 20th century. He left an outlasting legacy to both criminology and victimology. His contributions are characterized by their creativity, their originality and their clarity. To remedy what he saw as a terrible injustice done to crime victims he outlined a court procedure that restores the participants’ right to their own conflict, a procedure that provided the theoretical underpinnings of the restorative justice movement. He drew attention to the fact that victimization is not an objectively defined phenomenon but is a personal, relative and highly subjective experience. He insisted that mental images of those subjected to the same victimizing act could be and usually are quite varied. Criminology and victimology owe much to Nils Christie. The present article briefly highlights just a few of his significant contributions.